Anodic activity of boron-doped diamond electrodes in bleaching processes: effects of ultrasound and surface states - Holt, K; Forryan, C; Compton, R; Foord, J; Marken, F (2003)
In this study three types of polycrystalline highly boron-doped (ca. 1020 cm-3) diamond electrodes are compared with respect to their activity in anodic bleaching processes. A commercially available boron-doped diamond electrode (from De Beers), a conventional polycrystalline boron-doped diamond electrode grown in a hot filament chemical vapour deposition (HFCVD) process, and an sp2-carbon impurity state-rich polycrystalline boron-doped diamond electrode (grown in the presence of a high methane concentration) are characterized by voltammetry, Raman spectroscopy, and electron microscopy methods. Next, the efficiency of anodic bleaching processes (assumed to be based on hydroxyl radical generation at the diamond electrode surface) is investigated as a function of surface modification and with/without activation by power ultrasound. As a model process, the bleaching of the spin trapping reagent N,N-dimethyl-p-nitrosoaniline (RNO), is employed. Power ultrasound is shown to drastically improve the rate of bleaching by increasing the rate of mass transport at the electrode|solution interface. However, the state of the diamond electrode surface is also important. Boron-doped diamond electrodes rich in sp2 carbon impurity states are initially more efficient in the bleaching process. Reactive intermediates, such as hydroxyl radicals, appear to be formed preferentially in the vicinity of impurity states. However, mass transport is the dominating parameter in controlling the efficiency of the bleaching process.